2021
DOI: 10.1021/acs.jpcc.1c07048
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Size-Dependent Singlet Fission and Exciton Dynamics in Amorphous TIPS-Pentacene

Abstract: Aqueous nanoparticle (NP) dispersions are commonly used as model systems for the spectroscopic study of singlet exciton fission (SF) in acenes such as 6,13-(triisopropylsilylethynyl)­pentacene (TIPS-Pn). However, the potential for particle size effects to complicate interpretation of results in such model systems is generally ignored. In this work, we study amorphous TIPS-Pn NP dispersions prepared by the re-precipitation method over a range of particle sizes. Time-resolved fluorescence and femtosecond transie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…SF yields ϕ SF and ϕ SF ′ for (a) amorphous TIPS-Pn NPs as a function of NP diameter and (b) PMMA/TIPS-Pn composite NPs as a function of PMMA/TIPS-Pn mass ratio, where a higher mass ratio corresponds to greater average separation between TIPS-Pn molecules. Data are taken from refs and . In these systems, T 1 is indistinguishable from 1 (T···T).…”
Section: Triplet-pair Excitonsmentioning
confidence: 99%
See 4 more Smart Citations
“…SF yields ϕ SF and ϕ SF ′ for (a) amorphous TIPS-Pn NPs as a function of NP diameter and (b) PMMA/TIPS-Pn composite NPs as a function of PMMA/TIPS-Pn mass ratio, where a higher mass ratio corresponds to greater average separation between TIPS-Pn molecules. Data are taken from refs and . In these systems, T 1 is indistinguishable from 1 (T···T).…”
Section: Triplet-pair Excitonsmentioning
confidence: 99%
“…Given the lack of delayed fluorescence in systems in which SF is exothermic (such as pentacene), it is hard to verify this assertion via the presence of phenomena such as the quantum beating observed in tetracene and rubrene. , It has been suggested that spin decoherence may be faster in more disordered systems, so the assumption that spin decoherence should be on a ns−μs time scale may not be reasonable for all systems. Regardless, it is expected that the 1 (T···T) state is electronically and chemically indistinguishable from free triplets, and as such, these states are grouped together in many studies. In experiments that probe spin resonance, such as magnetic-field dependence on delayed fluorescence or electron paramagnetic resonance spectroscopy, it is possible to infer the presence of 1 (T···T) rather than T 1 +T 1 if spin coherence is observed at a time when 1 (TT) can be ruled out. However, this information is absent in other methods commonly used to study SF (such as transient absorption spectroscopy) or in systems where there is no delayed fluorescence (such as exothermic SF systems), so the convention has become somewhat inconsistent.…”
Section: Triplet-pair Excitonsmentioning
confidence: 99%
See 3 more Smart Citations